The effects of import competition on domestic financial markets: The role of limits-to-arbitrage - DeLisle, R. Jared; Wang, Mengying; Yüksel, H. Zafer; Zaynutdinova, Gulnara R. (Journal of International Business Studies, 2024)
While prior studies investigate the consequences of globalization, there remains a notable gap in understanding the market efficiency implications associated with globalization-induced import competition. Through the lens of asset pricing, we explore the financial market consequences of import competition exposure (ICE) and find a dark side of globalization. Consistent with the managerial objectives theory, we show that ICE is associated with high cash flow volatility, information asymmetry, and firm uncertainty. Moreover, ICE is positively related to limits-to-arbitrage (LTA), market inefficiencies such as holding and transactions costs. We find that domestic firms with higher ICE earn larger stock return premiums than those with lower exposure and, consistent with the limits-to-arbitrage theory, we demonstrate that LTA play a positive moderating role in the ICE premium. The use of a natural experiment in our analyses provides additional robust support of our hypotheses. Our findings impact both portfolio management decisions and how firms should incorporate the ICE premium into their cost of capital. A key implication is that firms exposed to import competition should prioritize transparency (such as disseminate highly readable disclosures) in order to diminish information asymmetry and limits-to-arbitrage, which would consequently reduce their associated ICE premium.